THE ROLE OF GOLKAR PARTY WOMEN UNITS (KPPG) IN THE POLITICAL RECRUITMENT OF WOMEN LEGISLATIVE CANDIDATES: PERAN KESATUAN PEREMPUAN PARTAI GOLKAR (KPPG) DALAM REKRUTMEN POLITIK CALON LEGISLATIF PEREMPUAN - Sindi Oktavira; Lince Magriasti (SOSIOEDUKASI, 2023)
This research purpose to describe the role of the Golkar Party Women’s Unity (KPPG) in the women legislative candidate political recruitment, and what are the obstacles faced by KPPG in the political recruitment of female legislative candidates. The research background was a form of female legislative candidate political recruitment. This research uses a quasi qualitative design. The method that researchers use in this study is the simple research design (SRD) method. Test of validity from data using the technique by source triangulation. The techniques for data analysis use three proces, namely reduction of data, presentation of data, and make conclusions (verification). The research result shown that the form of political recruitment conducted by the Golkar Party KPPG is using a semi-open procedure, which means prioritizing its cadres first as the party’s internal strength. In addition, someone who has close ties to the party elite and often comes from that elite family or is called based on political patronage. Meanwhile, the obstacle to the female legislative candidate political recruitment is the internal obstacle they face, namely not all party officials and KPPG members want to nominate themselves to become candidates for DPRD, and external constraints are influenced by socio-cultural aspects, level of education and political experience, and family environment.